2008
DOI: 10.1177/000313480807400709
|View full text |Cite
|
Sign up to set email alerts
|

The Reverse J Arteriovenous Graft Configuration for Hemodialysis Access: Rationale, Technique, and Outcomes

Abstract: The long-term survival of patients on hemodialysis is often limited by the exhaustion of vascular access sites. A fundamental principle of vascular access surgery is that the arteriovenous (AV) access be placed as far distally in the arm as possible. This principle enhances the secondary patency of the AV grafts by preserving the proximal veins for AV graft revision and provides venous outflow for a new AV access to be placed more proximally in the extremity. The standard straight and looped AV graft configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The cost-effective utilization of these medications should be reconsidered, especially since the high cost of clopidogrel makes it unobtainable for some patients. 21 A recent randomized, double-blind, placebo study 14 conducted in 13 centers (including our institution) in the United States to evaluate the effect of Dipyridamole plus aspirin on hemodialysis graft patency has demonstrated a primary patency rate of 23% (95% confidence interval [CI], 22 18-28) at 1 year for patients on Dipyridamole plus aspirin versus 28% (95% CI, [23][24][25][26][27][28][29][30][31][32][33][34] in the placebo group. This study concluded that treatment with Dipyridamole plus aspirin can prolong the duration of primary-unassisted patency (hazard ratio, 0.82; 95% CI, 0.68-0.98; P ¼ .03).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost-effective utilization of these medications should be reconsidered, especially since the high cost of clopidogrel makes it unobtainable for some patients. 21 A recent randomized, double-blind, placebo study 14 conducted in 13 centers (including our institution) in the United States to evaluate the effect of Dipyridamole plus aspirin on hemodialysis graft patency has demonstrated a primary patency rate of 23% (95% confidence interval [CI], 22 18-28) at 1 year for patients on Dipyridamole plus aspirin versus 28% (95% CI, [23][24][25][26][27][28][29][30][31][32][33][34] in the placebo group. This study concluded that treatment with Dipyridamole plus aspirin can prolong the duration of primary-unassisted patency (hazard ratio, 0.82; 95% CI, 0.68-0.98; P ¼ .03).…”
Section: Discussionmentioning
confidence: 99%
“…The patients with loop or straight grafts were not associated with a significantly higher primary patency, although this has been echoed in other studies. 31,32 The most common cause of graft failure is venous outflow stenosis or obstruction; therefore, the ideal salvage procedure has to consider central venous outflow evaluation. Declotting procedures are usually done using percutaneous techniques or open surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…The most feared complication of prosthetic lower limb AVG is infection. An American study of 125 thigh AVG reported an overall infection rate of 41% resulting in a 9% limb loss (24). Thigh grafts are more likely to become infected than arm grafts.…”
Section: Complications Of Lower Limb Accessmentioning
confidence: 99%